(untitled) (Al-Qamar, 2021)
Ibn al-Mulaqqin-famous Shāfiʿī jurist, great Ḥadīth and Sīrah scholar Sheikh Sirāj al-Dīn Abū Ḥafṣ ʿUmar b. ʿAlī b. Aḥmad Ibn al-Mulaqqin (723–804/1323–1401), a writer of various voluminous volumes on variety of Islamic sciences mostly well-known prolific academic personality for his valuable scholarship in the field of ḥadīth, Sīrah, fiqh, history and Muslim mysticism. AlʿAsqalānī (d. 852 A.H.) the famous Egyptian scholar of Hadith and author of magnum opus “Fatḥ al-Barī”, was one of his disciple. While engaging himself in different academic aspects of hadith, he also penned down prolifically on numerous other aspects as well. He has been admired by his disciples and successors too like AlʿAsqalānī, al-, al-’Irāqī, and sibt al-ʿajmī and others high ranked scholars in Muslim history. This study deliberates historical approach to describe Ibn al-Mulaqqin’s biographical sketch along with his contribution towards Muslim scholarship. In the last phase of this article, special focus has been centered on his “Ghāyah al-Sūl fī Khaṣāiṣ al-Rasūl” by exploring his methodology in detail.